Strategi Pemasaran Pupuk Kascing Pada Peternak Cacing Tanah - Sandi Ari Wijaya; Ahadiati Rohmatiah; Mutmainah Mutmainah (Coopetition : Jurnal Ilmiah Manajemen, 2022)
This study aims to analyze the marketing strategy of vermicompost for earthworm breeders in Kebonsari sub-district, Madiun district. This research is qualitative with the Grounded Research method. The population in this study were earthworm breeders in the Kebonsari sub-district, Madiun district, amounting to 5 people. Sampling was done through interview techniques. The analysis used is a SWOT matrix analysis, IE matrix, and the QSPM matrix. The results of the IFAS analysis is that it is classified as strong and able to take advantage of its business strengths and overcome its weaknesses. EFAS analysis indicates that the marketing of vermicompost is below average in its efforts to carry out strategies that take advantage of external opportunities and avoid threats. The results of the IE matrix show that vermicompost is in cell 5 (Growth Strategy/Stability Strategy) with concentration through horizontal integration. The results of the SWOT analysis obtained 5 alternative SO strategies, 6  WO strategies, 2 ST strategies and 4  WT strategies. The results of the QSPM matrix analysis show that earthworm breeders should use a market penetration strategy to market their vermicompost.